Nature's order? Questioning causality in the modelling of transport networks. Issue 97 (December 2018) - Vanoutrive, Thomas; De Block, Greet; Van Damme, Ilja
Highlights: Several studies naturalise the development of infrastructure networks. The growth of the Belgian motorway network is used as a case study. The underlying principles of natural science-inspired models need to be uncovered. The distinction made between 'politics' and 'rational factors' seems untenable. Recent uses of natural science metaphors fit well with Hayekian decentral planning. Abstract: Numerous social science studies found inspiration in the natural sciences to explain historical events and processes. Similarly, geography has a long history of scholarly work crossing boundaries between the natural and social sciences. A good example of such nature-society transfers is offered by the literature that models the spatial growth of infrastructure networks, ranging from the application of fractals, Newton's law of gravitation, and Shiatsu meridians, to laboratory experiments with slime mould in Petri dishes. This article focuses on how transfers between the social and natural sciences influence conceptualisations of causality, with the working hypothesis that economic thought has a key role in explaining the continued attraction. To reveal the particular ways in which researchers explain network development and try to uncover the underlying rationality and causality, two different approaches were applied to the same case, the development of Belgium's motorway network. The first approach is based on a quantitative topological gravity-style model, while the second offers a historical account. The confrontation of both approaches confirms that the risk of 'naturalising' history lies in the downplaying of the role of agency and political choices. But what makes this study especially relevant is that it shows how evolutions in economic thought shape the use of natural metaphors in novel ways, reinterpreting history using recent conceptualisations of demand, decentral planning, and the market/politics divide.